PENGARUH EDUKASI MEDIA VIDEO TERHADAP PENGETAHUAN IBU DALAM PENANGANAN CHOKING PADA BALITA DI WILAYAH KERJA PUSKESMAS SIMPANG TIGA KOTA PEKANBARU - Carles, Carles; Rulen, Betty Nia; Fitria, Eliza; Rufsonia, Puja (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Choking is an emergency situation that needs to be treated immediately; delayed treatment can result in death. Choking results in a blockage that obstructs breathing and restricts the passage of oxygen and alters gas exchange in the lungs. Parental knowledge is essential in the first aid treatment of choking in children. One way to overcome choking is to increase maternal knowledge by providing education through videos about handling choking. The purpose of this study was to determine the effect of video media education on maternal knowledge in handling choking in toddlers in Sidomulyo Timur Village, Simpang Tiga Health Center Working Area, Pekanbaru City. This study used a quasy-experiment design with a pre-post test without control group design. Data collection was done by using questionnaires on mothers as many as 98 respondents. Analysis was done by univariate analysis and bivariate analysis using Wilcoxon test. The statistical test results obtained Pvalue = 0.000 (p <0.05) which means there is an effect of providing video media education on maternal knowledge in handling choking in toddlers in Sidomulyo Timur Village, Simpang Tiga Puskesmas Working Area, Pekanbaru City. It is recommended that the Puskesmas can improve choking first aid skills and make IEC programs using educational videos about choking handling for all mothers of toddlers in their working area.Keywords : choking, knowledge, video media, toddler